2018
DOI: 10.1093/humupd/dmy012
|View full text |Cite
|
Sign up to set email alerts
|

How uterine microbiota might be responsible for a receptive, fertile endometrium

Abstract: The complex interplay of processes and cells involved in healthy pregnancy is still poorly understood. The correct receptive endometrial state, including the local immune environment, is crucial not only for fertility but also placenta formation since initiation of placentation highly depends on interaction with immune cells. Implantation failure, recurrent pregnancy loss, and other pathologies of endometrium and placenta, such as pre-eclampsia, represent an increasing societal burden. More robust studies are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
169
0
14

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 216 publications
(210 citation statements)
references
References 208 publications
5
169
0
14
Order By: Relevance
“…The uterine microbiome of women and cows suffering from endometritis differs from that of healthy females [92], suggesting that endometritis is associated with commensal microbiome dysbiosis [88]. Invasion of the uterine cavity in mares and other mammals mostly occurs via ascending migration from the vagina [86,93], in association with one or more reproductive problems as described above.…”
Section: Infectious Endometritismentioning
confidence: 99%
“…The uterine microbiome of women and cows suffering from endometritis differs from that of healthy females [92], suggesting that endometritis is associated with commensal microbiome dysbiosis [88]. Invasion of the uterine cavity in mares and other mammals mostly occurs via ascending migration from the vagina [86,93], in association with one or more reproductive problems as described above.…”
Section: Infectious Endometritismentioning
confidence: 99%
“…The endometrium has an innate immune system called pattern recognition receptors (PRR) that can detect certain pathogenic receptor patterns locally and mount an inflammatory response. Examples include toll like receptors 1-10, Nod like receptors, and others (71). Some have suggested that local bacteria can also use the PRR as a way to communicate with the host and induce a safe environment (72).…”
Section: Normal and Abnormal Immunological Responses To Pregnancymentioning
confidence: 99%
“…Nowadays, evidence from NGS investigations strongly supports the existence of a uterine microbiota and metagenomic approaches are gaining momentum in the analyses of the human endometrial microbiota under different conditions. Several reviews and commentary articles are already available on this specific topic [5][6][7][8][9][10][11][12]. Besides advances in the knowledge of the microbiota composition and its origin, these studies can also help to establish possible correlations between microbiota composition and uterus specific physiologic or pathologic conditions, including pregnancy, sterility, and conditions in which assisted reproductive technologies (ART) are adopted.…”
Section: Introductionmentioning
confidence: 99%
“…All these studies did not define a clear scenario of the human uterine microbiota and its dynamics in either physiological or pathological conditions, and some discrepancies can also be observed among the various analyses (for critical evaluations see the above cited reviews). It must be underlined, however, that the characterization of the uterine microbiome is particularly difficult, mainly due to possible contaminations occurring during trans-vaginal sampling and the low bacterial abundance of the site [9,10,12,24]. Clearly, further studies are required to establish the microbiota composition(s) of this site in its various physiological and pathological conditions.…”
Section: Introductionmentioning
confidence: 99%